Efficiency of Iranian Hospitals Before and After Health Sector Evolution Plan: A Systematic Review and Meta-Analysis Study - Amini, Saeed; Karami Matin, Behzad; Didehdar, Mojtaba; Alimohammadi, Ali; Salimi, Yahya; Amiresmaili, Mohammadreza; Kazemi-Karyani, Ali (Frontiers in Public Health, 2021)
Purpose: Aging, chronic diseases, development of expensive and advanced technologies has increased hospitals costs which have necessitated their efficiency in utilization of resources. This systematic review and meta-analysis study has assessed the efficiency of Iran hospitals before and after 2011 Health Sector Evolution Plan (HSEP). Methods: Internal and external databases were searched using specified keywords without considering time limitations. The retrieved articles were entered to EndNote considering inclusion and exclusion criteria and the final analysis was performed after removing duplicates. Heterogeneity between the studies was assessed using Q and I2 tests. Forest plot with 95% Confidence Interval (CI) used to calculate different types of efficiency. The data were analyzed using STATA 14. Results: Random pooled estimation of hospitals technical, managerial and scale efficiencies were 0.84 (95%CI = 0.78, 0.52), 0.9 (95% CI= 0.85,0.94) and 0.88 (95%CI= 0.84, 0.91), respectively. Sub-group analysis on the basis of study year (before and after HSEP in 2011) indicated that random pool estimation of technical (0.86), managerial (0.91) and scale (0.90) efficiencies of Iran hospitals for 2011 and before were better than technical (0.78), managerial (0.86) and scale (0.74) efficiencies after 2011. Conclusion: Type of hospitals’ ownership was effective on hospitals efficiency. However, HSEP has not improved hospitals efficiency, so that it is necessary to future national plans consider all aspects. Keywords: Efficiency, Hospital, Ownership, Costs, Iran